Molecular characterisation and biofilm production in Staphylococcusaureus isolates from the dairy production chain in Northern Italy. (April 2019) - Filipello, V.; Di Ciccio, P.A.; Colagiorgi, A.; Tilola, M.; Romanò, A.; Vitale, N.; Losio, M.N.; Luini, M.; Zanardi, E.; Ghidini, S.; Ianieri, A.; Finazzi, G.
Abstract: Staphylococcus aureus is able to produce enterotoxins causing staphylococcal food poisoning, and is frequently harboured by dairy products. Also, S . aureus is able to form biofilm in the production environment, enhancing the risk of food contamination. The ability of 49 S . aureus isolates from the dairy production chain to form biofilm aim was tested, and their genetic diversity in terms of population structure and presence of genes involved in biofilm formation or enterotoxins production was explored. The majority of the genotypes found were generally bovine associated; however, some have been also reported frequently in human clinical cases. Two isolates were methicillin-resistant. In total, 38.7% of the isolates were biofilm producers, and among them 47.3%, 42.1% and 10.5% exhibited weak, moderate, or strong biofilm-forming ability, respectively. In total 68% of the biofilm producing isolates were also positive for enterotoxins genes, raising concerns for consumer safety.